1995
DOI: 10.1002/ajmg.1320580306
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary spherocytic anemia with deletion of the short arm of chromosome 8

Abstract: We describe a 30-month-old boy with multiple anomalies and mental retardation with hereditary spherocytic anemia. His karyotype was 46,XY,del(8)(p11.23p21.1). Genes for ankyrin and glutathione reductase (GSR) were localized to chromosome areas 8p11.2 and 8p21.1, respectively. Six patients with spherocytic anemia and interstitial deletion of 8p- have been reported. In these patients, severe mental retardation and multiple anomalies are common findings. This is a new contiguous gene syndrome. Lux et al. [1990: N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…3) (Cau et al, 2005;Chilcote et al, 1987;Cohen et al, 1991;Dode et al, 2003;Kitatani et al, 1988;Lux et al, 1990;Okamoto et al, 1995;Stratton et al, 1992;Tsukahara et al, 1995;Vermeulen et al, 2002). This region is known to be the region responsible for the clinical entities associated with Kallmann syndrome and hereditary spherocytosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3) (Cau et al, 2005;Chilcote et al, 1987;Cohen et al, 1991;Dode et al, 2003;Kitatani et al, 1988;Lux et al, 1990;Okamoto et al, 1995;Stratton et al, 1992;Tsukahara et al, 1995;Vermeulen et al, 2002). This region is known to be the region responsible for the clinical entities associated with Kallmann syndrome and hereditary spherocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…One of the genes responsible for hereditary spherocytosis is ankyrin 1 gene (ANK1), located on 8p11.21 (Lux et al, 1990); many mutations of ANK1 have been reported to date (Eber et al, 1996;Miraglia del Giudice et al, 1998). Because haploinsufficiency of ANK1 can cause hereditary spherocytosis, some patients with 8p11.2 deletions have been reported to display hereditary spherocytosis (Cau et al, 2005;Okamoto et al, 1995).…”
Section: Introductionmentioning
confidence: 98%
“…In the remaining 25% of patients autosomal recessive (AR) and de novo mutations were observed (Table 1). In rare cases, HS can be associated to psychomotor developmental delay and autism in contiguous gene syndromes due to large genomic deletions, including ANK1 20,21 or SPTB genes. 22,23 Finally, prenatal hydrops fetalis has been rarely observed in patients with mutations in SLC4A1 24 and SPTA-SPTB genes.…”
mentioning
confidence: 99%
“…There have also been several reviews on del 8p involving a total of 39 cases (Digilio et al, 1998;Okamoto et al, 1995;Wu et al, 1996). Individuals with del 8p are reported to share a distinctive pattern of clinical features, including low birth weight, growth restriction, intellectual disability, congenital heart defects, microcephaly, and mild facial anomalies (Digilio et al, 1998).…”
Section: Discussionmentioning
confidence: 98%